As a fraction, it would be 5 6/10. Then you multiply the denominator by the whole number 5x10 and add the numerator. So,
10X5+6=56
56/10
divide by 2
28/5 is the simplified version
Hi, ok all you need to do is use the direct variation formula which is= y/x=y/x so you will replace your numbers by each value which get us to = 3/-6=y/1 so you cross multiply which gives us 3=-6y you divide 3 by -6 and that is the value of y, thank you for reading hope it helps ;)
For #2:
<span> 3x^2 + 4 – 2x^2 + 6</span>
<span><span>You need to combine your like terms:
</span>
3x^2 – 2x^2= x^2</span>
4 + 6 = 10
This will now give you:
<span>X^2 +10</span>
If you begin with the basic equation of a vertical parabola: y-k=a(x-h)^2, where (h,k) is the vertex, then that equation, when the vertex is (-3,-2), is
y + 2 = a (x + 3)^2. If we solve this for y, we get
y = a(x+3)^2 - 2. Thus, eliminate answers A and D. That leaves B, since B correctly shows (x+3)^2.
Answer:
4,450
Step-by-step explanation:
You muiltiply 250 times 15 then you add 700